Health-related quality of life among stroke survivors in Kano, Nigeria: A mixed-method study / Ashiru Hamza Mohammad - Mohammad, Ashiru Hamza (2014)

(untitled)
Background: Cerebrovascular accident or stroke is currently the main cause of neurological disability in Nigeria with devastating impact on the person’s physical, psychological, and social functioning. Some stroke survivors are able to adapt to their disabilities while others are devastated even by a minor sequelae. In the Nigerian healthcare model, the focus is on survival only, thus overshadowing all other, broader Quality of life (QOL) issues. This study aims to determine the factors that have an impact on the quality of life of stroke survivors and to highlight why and how these individuals retain or lose their sense of wellbeing after stroke in Kano, Nigeria. Method: This is a mixed-method study conducted in three phases on 233 stroke survivors in Kano, Nigeria. Phase I is the validation of the primary tools for the measurement of QOL and social support. Phase II (quantitative phase) is a longitudinal study to identify the domain specific covariates (predictors) of QOL at 6 months and 1 year after stroke. In Phase III (qualitative phase), data were collected via in-depth interviews with 15 participants with the aim to explore the factors identified in Phase II. Correlations and stepwise linear regression model were used to determine the domain specific covariates (predictors) of QOL, whilst thematic analysis using constant comparative methods aided by NVivo 9 software was used to analyse the qualitative data. Finally, an integration of the phases for an overall presentation of the health-related quality of life of these survivors was discussed. Results: The 16-item Hausa (language) version of the Stroke Impact Scale (Hausa-SIS) 3.0’s 8 domains (strength, hand function, mobility, activities of daily living (ADL), emotion, memory, communication and social participation) was found to be psychometrically fit and have good coverage of Quality Of Life (QOL) construct. In the final analysis, a parsimonious model was obtained with two items for each of the 8 constructs. The 11-item Hausa version of the Multidimensional Scale of Perceived Social Support (Hausa-MSPSS) was found to be reliable and acceptable for the assessment of perceived social support among stroke survivors in Nigeria. A two-factor model with Family and Friends as the two domains was found to be acceptable. Phase II results showed that among the eight dimensions of QOL, all dimensions excluding the emotional domain, showed significant improvement at 1 year after stroke. However, social support was significantly decreased from 6 months to 1 year after stroke v (p<0.005). Linear regression showed that the factors found to be most predictive of satisfactory QOL at 6 months after stroke are being employed, enough income, presence of a caregiver, acceptance at work place, higher level of education, side of stroke, less dependency in conducting activities of daily living (Barthel Index Score), urban residency, lower degree of disability (Modified Rankin Score), and higher degree of social support. The factors “reasonable hospital treatment charges” and “perceived social support by friends” were found to be additional predictors of satisfactory QOL at 1 year after stroke. Withdrawal of support by significant others was the sole factor associated (p<0.05) with unsatisfactory QOL at both 6 months and at 1 year after stroke. The qualitative study revealed that in addition to the factors above, the availability and accessibility of spiritual and religious resources as well as the ability to perform sexually and other functions and the received social support helped the stroke survivors to improve the emotional domain of their QOL. Conclusion: Stroke has debilitating consequences affecting many aspects of functioning and living. To improve the QOL of the stroke survivors, it is recommended that programs that focus on meeting their needs such as re-employment, religious and socio-cultural activities plus continual social and financial support should be developed and given to them as part of a holistic rehabilitation program for stroke patients and survivors. Keywords: stroke survivors, quality of life, satisfaction, mixed-methods research design, Nigeria